Characterization of two flavonol synthases with iron-independent flavanone 3-hydroxylase activity from Ornithogalum caudatum Jacq - Sun, Yu-Jia (BMC Plant Biol, 2019)
BACKGROUND: Flavonol synthase (FLS) is the key enzyme responsible for the biosynthesis of flavonols, the most abundant flavonoids, which have diverse pharmaceutical effects. Flavonol synthase has been previously found in other species, but not yet in Ornithogalum caudatum. RESULTS: The transcriptome-wide mining and functional characterisation of a flavonol synthase gene family from O. caudatum were reported. Specifically, a small FLS gene family harbouring two members, OcFLS1 and OcFLS2, was isolated from O. caudatum based on transcriptome-wide mining. Phylogenetic analysis suggested that the two proteins showed the closest relationship with FLS proteins. In vitro enzymatic assays indicated OcFLS1 and OcFLS2 were flavonol synthases, catalysing the conversion of dihydroflavonols to flavonols in an iron-dependent fashion. In addition, the two proteins were found to display flavanone 3β-hydroxylase (F3H) activity, hydroxylating flavanones to form dihydroflavonols. Unlike single F3H enzymes, the F3H activity of OcFLS1 and OcFLS2 did not absolutely require iron. However, the presence of sufficient Fe(2+) was demonstrated to be conducive to successive catalysis of flavanones to flavonols. The qRT-PCR analysis demonstrated that both genes were expressed in the leaves, bulbs, and flowers, with particularly high expression in the leaves. Moreover, their expression was regulated by developmental and environmental conditions. CONCLUSIONS: OcFLS1 and OcFLS2 from O. caudatum were demonstrated to be flavonol synthases with iron-independent flavanone 3-hydroxylase activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1787-x) contains supplementary material, which is available to authorized users.